Subacute infectious endocarditis-associated membranoproliferative glomerular nephritis: A Case Report and Review - Zhang, Yi De; Yu, Ya Min; Dai, Hou Yong; Chen, Xiao Lan; Yuan, Li; Shi, Hui (Journal of Cardiology and Cardiovascular Medicine, 2017)
We experienced a case of membranoproliferative glomerulonephritis (MPGN) caused by subacute infectious endocarditis (SIE). A 57-year-old male farmer complained of fatigue, lack of appetite and gross haematuria for a month; he had no cough, chest pain, or exertion dyspnea. After admission, lab tests showed mild proteinuria(1.04g/d) and heavy dysmorphic red blood cells(RBC) (543/HP), with serum creatinine(Scr) slightly elevated(1.46mg/dl) and anemia(hemoglobin Hb 85g/L). A renal biopsy revealed MPGN lesion with 16.6% cellular crescents. The echocardiogram test revealed mitra valve prolapse with perforation of the anterior lobe, vegetation, and severe regurgitation. He was diagnosed as SIE induced MPGN. Then he underwent mitral valve replacement after systemic antibiotic treatment without immunosuppressive agents. Follow-up showed that he dramatically regained normal kidney function in total 1 year after the operation. Thus, antibiotic administration and valve replacement may be efficient enough for some of SIE induced MPGN. We did a brief review of the literature on SIE induced MPGN, which was sometimes misdiagnosed due to its silent characteristics; some SIE patients may initially have other organs involved.